2020
DOI: 10.1021/acs.langmuir.0c02350
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Responsive Oil-In-Dispersion Emulsions Stabilized by Similarly Charged Ferrocene Surfactants and Alumina Nanoparticles

Abstract: A redox-responsive oil-in-dispersion emulsion was developed by using a cationic ferrocene surfactant (FcCOC 10 N) and Al 2 O 3 nanoparticles, in which the required concentrations of FcCOC 10 N and Al 2 O 3 nanoparticles are as low as 0.001 mM (≈0.005 cmc) and 0.006 wt %, respectively. Rapid demulsification can be successfully achieved through a redox trigger, resulting from the transition of FcCOC 10 N from a normal cationic surfactant form into a strongly hydrophilic Bola type form (Fc + COC 10 N). Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low. [36,37] Here, we believe that only NaDC molecules adsorb at the oil-water interface with silica particles dispersed in the continuous phase between droplets [31][32][33][34][35] producing an oil-indispersion emulsion [35] as shown by the SEM and fluorescence microscopy images (Figures 2 and S7). It was further observed that this strategy of improving the emulsifying ability of BS by addition of silica particles is universal for other BS.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low. [36,37] Here, we believe that only NaDC molecules adsorb at the oil-water interface with silica particles dispersed in the continuous phase between droplets [31][32][33][34][35] producing an oil-indispersion emulsion [35] as shown by the SEM and fluorescence microscopy images (Figures 2 and S7). It was further observed that this strategy of improving the emulsifying ability of BS by addition of silica particles is universal for other BS.…”
Section: Resultsmentioning
confidence: 81%
“…The fluorescence image (particles labelled green in Figure S7) also proves the position of the particles is mainly in the aqueous continuous phase. [31][32][33][34][35] This microstructure is different from that of Pickering emulsions stabilized by NaDC and positively charged alumina nanoparticles (Figure 2d), in which particles attach to the oilwater borders forming winkled films on the surfaces of dried oil droplets. We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Responsive emulsifiers have emerged as a class of smart surfactants that permit regulating the emulsion stability under external stimuli [4][5][6][7][8]. The external stimuli include pH [9][10][11][12][13][14][15], CO 2 [6,16], temperature [17], magnetism [8], light [18,19], and redox [7,20]. Among these external stimulation types, pH has attracted particular interest because it has the advantage of being simple to regulate [11,21].…”
Section: Introductionmentioning
confidence: 99%